"I put a stone on my heart and kept going": An explanatory model of how distress is generated and regulated among Indian women from slums reporting gender-based violence. (August 2022) - Patel, Anushka R.; Kovacevic, Merdijana; Hinton, Devon; Newman, Elana
Clinical variation in the expression of panic disorder, depression and anxiety, and posttraumatic stress disorder (PTSD) has have been documented across cultures. However, local (emic) cultural models that explain how people make sense of their illness experiences remain relatively understudied in India among trauma-exposed populations. Further, the integration of emic findings into clinical care is limited, underscoring the need for emic perspectives following trauma to improve the development or adaptation of trauma-focused treatments in India. This study describes an emic explanatory model of distress, which includes idioms of distress, perceived causes of distress, and coping/help-seeking behaviors among Indian women from slums reporting gender-based violence. This explanatory model can be used as a culturally grounded way to develop clinical case conceptualizations to adapt and deliver psychological treatments for this under-served population.